Pengaruh Latihan Self-talk Positif untuk Meningkatkan Kepercayaan Diri terhadap Akurasi Memanah (Atlet Panahan PERPANI Kudus) - Izzah, Aqidatul; Setyawati, Heny (Universitas Negeri Semarang, 2023)
Archery is a sport that uses archery accuracy as its main element. To improve archery accuracy, mental training is needed. This study aims to determine the effect of positive self-talk exercise to increase confidence in the archery accuracy of PERPANI Kudus archery athletes. This research is an experimental study with a research design of One Group Pretest and Posttest, the research subjects are all 17 Perpani Kudus athletes. The data analysis technique uses the paired sample t test. The results of the paired sample t test for self-confidence, obtained the t count (9.111) > t table (1.746) with a 2-tailed significance value of 0.000 < (0.05). While the results of the calculation of the paired sample t test for archery accuracy obtained the value of t count (6.982) > t table (1.746) with a significance value (2-tailed) of 0.000 < (0.05). Based on the calculations that have been done, it is concluded that 1) there is an effect of positive self-talk exercise to increase the athlete's confidence, 2) there is an increase in confidence in the archery accuracy of archery athletes. Suggestions: 1) for athletes who still have a low level of self-confidence and accuracy to be able to improve it with positive self-talk exercises, 2) for coaches to pay more attention to training for athletes, 3) for researchers should be able to carry out research with samples, populations that are wider and add comparison variables.